Bidirectional association between rheumatoid arthritis and chronic obstructive pulmonary disease: a systematic review and meta-analysis - Wang, Meijiao; Pan, Hejing; Zhai, Yingqi; Li, Haichang; Huang, Lin; Xie, Zhijun; Wen, Chengping; Li, Xuanlin (Frontiers in Immunology, 2024)
BackgroundRheumatoid arthritis (RA) and chronic obstructive pulmonary disease (COPD) are prevalent and incapacitating conditions, sharing common pathogenic pathways such as tobacco use and pulmonary inflammation. The influence of respiratory conditions including COPD on RA has been observed, meanwhile RA may constituting one of the risk factors for COPD. It unclear that whether a bidirectional associate between RA and COPD. Our study aims to explore the bidirectional relationship between RA and COPD.MethodsWe systematically searched PubMed, Cochrane Library, and Embase for observational studies from the databases inception to February 20, 2024, utilizing medical subject headings (MeSH) and keywords. We included studies in which RA and COPD were studied as either exposure or outcome variables. Statistical analyses were conducted employing STATA software (version 14.0). The relationship was reported as odds ratios (OR) and corresponding 95% confidence intervals (CI). Publication bias was assessed using funnel plots and Egger’s regression.ResultsNineteen studies with 1,549,181 participants were included. Risk of bias varied from low to moderate, with evidence levels rated as low or very low. Pooled analysis revealed a significant association between RA and increased COPD risk (OR=1.41, 95%CI 1.13 to 1.76, I2 = 97.8%, P=0.003). Subgroup analyses showed similar COPD risk elevations in both of genders, seropositive/seronegative RA, cohort and case control studies. Additionally, there was a significant RA risk increase among those with COPD (OR=1.36, 95%CI 1.05 to 1.76, I2 = 55.0%, P=0.022), particularly among females and seropositive RA, and cohort studies.ConclusionThe meta-analysis identifies a significant bidirectional association between RA and COPD, emphasizing mutually increased risk. Recognizing this connection may can inform proactive approaches to disease prevention and management, potentially reducing the public health burden and improving quality of life.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024518323.